Exploring the antimicrobial properties of vaginal Lactobacillus crispatus against preterm birth-associated bacteria. Issue 3 (1st August 2022) - Amabebe, Emmanuel; Bhatnagar, Noopur; Kamble, Nitin; Reynolds, Steven; Anumba, Dilly O
Abstract : Lay summary: The need to develop new treatments to prevent unprompted premature delivery before 37 weeks of pregnancy remains pressing and unmet. Bacteria ( Lactobacillus species) that promote vaginal health produce biochemical compounds that prevent the growth of microbes such as Gardnerella vaginalis . Overgrowth of G. vaginalis can cause vaginal infection with smelly discharge and increase a woman's risk of sexually transmitted infections and premature delivery. In this study, we examined how normal health-promoting ( L. crispatus ) and potentially harmful ( G. vaginalis ) vaginal bacteria interact in a laboratory setting. This was in order to observe natural and effective agent(s) from L. crispatus that can hinder the growth of G. vaginalis and accompanying immune response. We observed that L. crispatus clears G. vaginalis by itself and with several biochemical compounds that it produces. Such biochemical compounds can be developed into treatment for vaginal infections and premature delivery due to infection and inappropriate immune response.